PENERAPAN TEKNOLOGI PENGENDALIAN HAMA TERPADU (PHT) PADA PERKEBUNAN RAKYAT JAMBU METE (Studi Kasus Petani Jambu Mete di Propinsi Nusa Tenggara Barat) - SUPRIATNA, ADE (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
This study was conducted in 2003 and took place in Nusa Tenggara Barat (NTB). The objectives of study were: to evaluate the implementation of the integrated pest management School on farmer field (IPM-FFS), farmers adoption of IPM technology, changes of farm productivity and income. The result showed, that majority of farmers have controlled the pest based on principles of IPM. Firstly, the farmer do preventive control by adopting some practices to make crops grow healthy, apply biological and mechanical control, and also use organic pesticide. Finally, if the intensity of pest's attack were still in the level of economic injury the farmer would use chemical pesticide. Agroecosystem observation has been adopted by alumni farmer (100%) and non-alumni (34, 5%), mechanical control have been adopted by (100%) and non-alumni (66, 6%), and organic pesticide have been adopted by alumni (6, 7%) and non-alumni (13, 3%). While the application of chemical pesticide not be found because the intensity of pest attack was still low and the costly pesticide price push reduction of chemical pesticide use. The alumni productivity was 300kg and non-alumni were 270 kg/ha/year. If all expenses of farm were counted, farm benefit of alumni and non-alumni would be disadvantage, namely Rp.206 thousand and Rp.287 thousand/ha/year, respectively. If family labor cost were not counted, they would be advantage, namely Rp.858 thousand and Rp.735 thousand/ha/year, respectively. Then if all expenditure coming from property of farmer (family labor and organic fertilizer) were not counted, they would be advantage, namely Rp.890 thousand and Rp.771 thousand/ha/year, respectively. Based on statistical test, productivity and farm benefit of alumni and non-alumni were not different. Introducing the low cost technology (IPM-FFS) is very suited for cashew nut farmer because their capital are still low such as using organic pesticides available in their field, biological and mechanical control, and organic manure. Considering its progress, IPM-FFS is suggested to overspread to other location.
Keywords: Integrated Pest Management; Cashewnut; Farmers